1995
DOI: 10.1007/bf00352359
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the diabetes polygene Idd3 on mouse Chromosome 3 by use of novel congenic strains

Abstract: Development of novel congenic mouse strains has allowed us to better define the location of the diabetogenic locus, Idd3, on Chromosome (Chr) 3. Congenic strains were identified by use of published and newly developed microsatellite markers, their genomes fingerprinted by a rapid, fluorescence-based approach, and their susceptibility to type 1 diabetes evaluated. The maximum interval containing Idd3 is now approximately 4 cM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…The strain NOD.B10Idd5R1 (N8F2-4), referred to as Idd5R1, was the founding congenic strain and contains the greatest amount of introgressive B10 DNA. Founders of the Idd5R1 strain were tested for the presence of B10 chromosomal segments throughout the genome using a panel of microsatellite markers that differentiate NOD and B10 genomic segments (20). All non-chromosome 1 markers examined were of NOD origin in the Idd5R1 strain.…”
Section: Methodsmentioning
confidence: 99%
“…The strain NOD.B10Idd5R1 (N8F2-4), referred to as Idd5R1, was the founding congenic strain and contains the greatest amount of introgressive B10 DNA. Founders of the Idd5R1 strain were tested for the presence of B10 chromosomal segments throughout the genome using a panel of microsatellite markers that differentiate NOD and B10 genomic segments (20). All non-chromosome 1 markers examined were of NOD origin in the Idd5R1 strain.…”
Section: Methodsmentioning
confidence: 99%
“…The derivation of the congenic strains R450 (N13F5-6) and NOD.B6 Idd10R2 (N8F9) has been previously described (9,14). During their development, progenitor mice for both strains were tested for the presence of non-NOD-derived DNA at microsatellite markers spread across the genome and were found to be NOD at all loci (10). The congenic strains NOD.…”
Section: Methodsmentioning
confidence: 99%
“…NOD. B6 Idd3 mice, introgressed with the protective T1D-resistant Idd3 locus, show a marked resistance to reduced T1D onset (15,18,19), while also affecting susceptibility to other organ-specific autoimmune diseases like experimental autoimmune encephalomyelitis and ovarian disease provoked by day 3 thymectomy (20,21). Interestingly, fine mapping and positional cloning studies of the Idd3 B6 locus have demonstrated that the Il2 gene is the primary candidate for Idd3-mediated protection in a model of CD8 ϩ T cell-induced T1D and a likely contributor to increased CD4 ϩ T reg cell activity in these mice (19,22).…”
Section: Foxp3mentioning
confidence: 99%